Implementation of Quality Management in Improving Services Education at SD Negeri 2 Karawang - Taufik Ismail, Achmad (Program Studi Manajemen Pendidikan Islam, 2024)
The achievement of educational goals depends on the quality of educational institutions. In the school context, educational quality is related to the effectiveness of educational services provided in accordance with the intended objectives. Educational quality encompasses two main aspects: process and outcome. School management plays a crucial role in achieving the desired quality, making it essential for school principals, teachers, education staff, and the community to share a common understanding of education and its implementation. This study aims to analyze various aspects of educational quality at State Elementary School 2 Karawang Kulon. Using a qualitative approach, the research examines educational services through interviews, observations, and documentation. The study focuses on the efforts of school principals to improve educational services, teachers' strategies to enhance teaching competencies, and the evaluation of education staff performance. Additionally, this research assesses students' satisfaction with the available facilities and services. The findings are expected to provide insights into strategies for improving the quality of primary education and offer recommendations for stakeholders in enhancing educational services.